A game of thrones : the graphic novel, volume 2 - Abraham, Daniel (Bantam Books, 2013)
In this second volume, the action moves from the icy north, where the bastard Jon Snow seeks to carve out a place for himself among the bitter outcasts and hardened criminals sworn to service upon the Wall...to the decadent south and the capital city of King's Landing, where Jon's father, Lord Eddard Stark, serves as the Hand of King Robert Baratheon amid a nest of courtly vipers...to the barbarian lands across the Narrow Sea, where the young princess Daenerys Targaryen has found the unexpected in her forced marriage to the Dothraki warlord Khal Drogo: love -- and with it, for the first time in her life, power. Meanwhile, the dwarf Tyrion Lannister, accused by Lady Catelyn Stark of the attempted murder of her son, must call upon all his cunning to survive imprisonment in the dungeons of the Eyrie, where Lady Stark's sister rules.